The Role of Depression in the Effect of Technology-Facilitated Sexual Violence on Suicidal Ideation in Early Adult - Salma Ghina Sakinah Safari; Margaretha Margaretha (Faculty of Psychology, Universitas Gadjah Mada, 2022)
The phenomenon of suicide ideation is a problem that needs to be examined at this time. This study investigates the role of technology-facilitated sexual violence experience and depression on the appearance of suicidal ideation in emerging adults. A quantitative research was conducted on a sample of 322 respondents aged 18–25 years. Three scales were used in this research: the Technology-Facilitated Sexual Violence Victimization Scale is established by Henry & Powell (2014), to measure the respondents’ technology-facilitated sexual violence experiences; Lovibond & Lovibond’s (1995) Depression, Anxiety, Stress Scale to measure the respondents’ depression, anxiety, and stress; and Beck’s (1979) Scale of Suicidal Ideation established to measure the appearance of the respondents’ suicide ideation. The data were analyzed using the statistical correlation test, multivariate linear regression hierarchy, and path analysis. From the results, technology-facilitated sexual violence was found to have a significant effect on suicidal ideation in early adults. Furthermore, it was found that depression partially mediates the relationship between technology-facilitated sexual violence and suicidal ideation in early adults. This study is beneficial to developing a positive internet intervention approach to create more conducive virtual spaces.